Current realities of home blood pressure monitoring from physicians’ perspectives: results from Asia HBPM survey 2020 - Wang, Tzung-Dau; Ohkubo, Takayoshi; Bunyi, Ma Lourdes; Chadachan, Veerendra Melagireppa; Chia, Yook Chin *; Kario, Kazuomi; Kim, Cheol-Hee; Lin, Hung-Ju; Matsushita, Noriko; Park, Sungha; Salman, Ebtehal; Sukonthasarn, Apichard; et al. (Sprinter Nature, 2023)
Uncontrolled hypertension is a significant problem in many parts of Asia. Effective management is essential to reduce the burden of hypertension. Home blood pressure monitoring (HBPM) is a promising tool that can aid in the diagnosis and management of hypertension. Experts from 11 countries/regions in Asia conceptualized a large-scale survey to examine the current realities of HBPM. A cross-sectional survey was conducted among health care professionals from China, India, Indonesia, Japan, Malaysia, the Philippines, Singapore, South Korea, Taiwan, Thailand, and Vietnam between November 2019 and June 2021. Physicians' responses were summarized using descriptive statistics. A total of 7945 physicians participated in the survey. Among all respondents, 50.3% and 33.5% viewed HBPM as highly recognized by physicians and patients in their country/region, respectively. Lack of understanding of HBPM and concern with the accuracy and reliability of HBPM devices were identified as key barriers to HBPM recognition. Nearly all physicians (95.9%) reported recommending HBPM to their patients; however, they reported less than 50% of their patients measured home blood pressure (HBP). Among physicians who recommended HBPM, only 22.4% and 54.1% cited HBP diagnostic threshold values and timing of taking antihypertensive drugs that were consistent with available guidelines, respectively. The survey reveals that the recognition of HBPM as a valuable tool to diagnose and manage hypertension is suboptimal in most parts of Asia. Despite high recommendation of HBPM to hypertensive patients by physicians, there are considerable discrepancies between guidelines recommendations and practice realities. The recognition of HBPM as a valuable tool for the diagnosis and management of hypertension is suboptimal among both physicians and patients in Asia. A clear and consistent guidance for proper HBPM practice and use of validated and calibrated HBP monitors are among the top priorities to support the integration of HBPM into daily patient care. HBPM: home blood pressure monitoring, HBP: home blood pressure.